Saharan dust electrification perceived by a triangle of atmospheric electricity stations in Southern Portugal - Silva, Hugo (2019)
Atmospheric Electric Potential Gradient (PG) measurements were carried out in three sites forming a triangular array in Southern Portugal. The campaign was performed during the summer, characterized by Saharan dust outbreaks; 16the17th July 2014 dust event is considered. Short time-scale oscillations of the PG at two of the stations and a mid time-scale suppression of the PG in the three stations are found. Results are interpreted as evidencing long-range dust electrification; attributed to the air-Earth electrical current creating a bipolar charge distribution inside of the dust layer. The relevance of using arrays of sensors, instead of single sited, is highlighted.